2010
DOI: 10.1111/j.1600-0722.2010.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries outcomes after orthodontic treatment with fixed appliances: do lingual brackets make a difference?

Abstract: Orthodontic treatment with fixed appliances is considered a risk factor for the development of white spot caries lesions (WSL). Traditionally, brackets are bonded to the buccal surfaces. Lingual brackets are developing rapidly and have become more readily available. Buccal surfaces are considered to be more caries prone than lingual surfaces. Furthermore, lingual brackets are shaped to fit the morphology of the teeth and seal almost the entire surface. In the present study we tested the hypothesis that lingual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 29 publications
1
59
0
11
Order By: Relevance
“…Previous research provides hints of a decreased incidence of WSL formation in subjects treated with lingual multi-bracket appliances when compared to labial fixed treatment [8]. In terms of prevention of those side-effects associated with longer treatment durations, the WIN appliance would clearly be the better choice, especially in cases of elevated malocclusion severity or treatment complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research provides hints of a decreased incidence of WSL formation in subjects treated with lingual multi-bracket appliances when compared to labial fixed treatment [8]. In terms of prevention of those side-effects associated with longer treatment durations, the WIN appliance would clearly be the better choice, especially in cases of elevated malocclusion severity or treatment complexity.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of reducing frequencies of enamel decalcification, the lingual bracket approach seems favorable [8], and reasons may be seen in enhanced saliva wetting and self-cleansing of enamel surfaces [9]. Moreover, considered as an esthetic benefit, lingual WSLs do not impair dentofacial appearance, which is otherwise a very frequent problem in finished cases treated with conventional labial-side MB.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to advantages shown for patients, the risk of developing white spot lesions appears to be drastically reduced when using lingual compared to labial appliances [7, 8, 15, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Van der Veen et al [3], in a prospective randomized split-mouth study, showed the incidence of white spot lesions (WSL) on the buccal surfaces around the labial brackets, to be almost five times higher than developing or progressing lesions found on the lingual surfaces with lingual brackets. Additionally, besides the number of lesions, their severity as measured by the integrated calcium loss, was on average ten times higher with labial fixed appliances than with lingual fixed appliances [3].…”
Section: Introductionmentioning
confidence: 99%